2012
DOI: 10.1152/ajpheart.00376.2012
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial cell sheet therapy and cardiac function

Abstract: Heart failure (HF) is the leading cause of death in developed countries. Regenerative medicine has the potential to drastically improve treatment for advanced HF. Stem cell-based medicine has received attention as a promising candidate therapy over the past decade; however, it has not yet realized this potential in terms of reliability. The cell sheet is an innovative technology for constructing aligned graft cells, and several cell sources have been investigated for making a feasible cell sheet. The most repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 115 publications
1
37
0
Order By: Relevance
“…The constructs used for cardiac tissue repair include the implantation of multicellular cardiospheres [18], various formulations of 2D cellular sheets [19][20][21][22], and various formulations of 3D tissues [5][6][7][8]13]. The composition of the noncellular constituents varies from minimal constituents for cardiosphere clusters to a range of ECM components [23,24] and growth factors [25][26][27] selected for their ability to facilitate CM survival and functional maturation.…”
Section: Various Formulations For Engineered Cardiac Tissuesmentioning
confidence: 99%
“…The constructs used for cardiac tissue repair include the implantation of multicellular cardiospheres [18], various formulations of 2D cellular sheets [19][20][21][22], and various formulations of 3D tissues [5][6][7][8]13]. The composition of the noncellular constituents varies from minimal constituents for cardiosphere clusters to a range of ECM components [23,24] and growth factors [25][26][27] selected for their ability to facilitate CM survival and functional maturation.…”
Section: Various Formulations For Engineered Cardiac Tissuesmentioning
confidence: 99%
“…It is also well known that myoblasts induced arrhythmia in the Myoblast Autologous Grafting in Ischemic Cardiomyopathy (MAGIC) trial for severe HF patients (4). Even though myoblasts were transplanted as cell sheets, they still provoked arrhythmia because myoblasts do not express connexin43 or N-cadherin, and have their own automaticity (5). On the other hand, CMs can connect with a host heart, inducing less risk of arrhythmia with transplanted CMs.…”
Section: Arrhythmogenicity After Cell Transplantation Therapiesmentioning
confidence: 99%
“…Several cell sources are potentially available for such therapy including bone marrow stem cells, myoblasts, and cardiac progenitor cells, while BMSCs and CPCs were shown to be safe in transplanted patients (2 -4). However, while all of these cell sources are functionally successful in small animal experiments, none has produced a marked improvement of cardiac function in large clinical studies (5). Thus, transplantation of purified cardiomyocytes (CMs) is eagerly awaited to achieve feasible and solid strategies for regenerative cardiac medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical trials in this area are ongoing; however, in general, large clinical trials have failed to show a marked improvement in cardiac function, despite most of the basic studies using small-animal models, such as mice or rats, showed a prominently significant improvement in cardiac function (>10% increase in LVEF) with cell therapies. 17 The valley of death between basic and clinical research in stem cell therapy demands the necessity for preclinical studies with large-animal models. The "Tissue-Engineered Heart Repair" session focused on how to achieve functional repair following the loss of large numbers of cardiomyocytes.…”
Section: Regenerative Medicine For CV Diseases Andmentioning
confidence: 99%